ChemInform Abstract: The Transition‐Metal‐Catalyst‐Free Oxidative Homocoupling of Organomanganese Reagents Prepared by the Insertion of Magnesium into Organic Halides in the Presence of MnCl2·2LiCl. Issue 11 (March 2015) - Peng, Zhihua; Li, Na; Sun, Xinyang; Wang, Fang; Xu, Lanjian; Jiang, Cuiyu; Song, Linhua; Yan, Zi‐Feng
Abstract In addition to the title homocoupling reaction the arylmanganese reagents also react with electrophiles or undergo palladium‐catalyzed cross‐coupling reactions.